The role of fetal heart rate in first trimester sonograms in prediction of fetal sex: a systematic review and meta-analysis - Shadi Nouri; Mohammad Hassan Kalantar; Fatemeh Safi; Amir Almasi-Hashiani (BMC, 2023)
Abstract Background Early fetal sex determination is worthy of providing alertness about possible x-linked disorders, as well as predicting sex-related pregnancy complications and outcomes. Satisfying the curiosity of parents is another advantage. In this way, several studies have been performed which have shown conflicting results. Aim We planned a systematic review for identifying any plausible role of Fetal Heart Rate (FHR) for early predicting fetal sex during the first trimester of non-complicated pregnancies. Methods This is a meta-analysis in which PubMed and Scopus databases were searched using different related keywords to find similar articles up to December 2022. Then the articles were screened to find eligible articles and finally, the articles entered in the meta-analysis were analyzed using Stata software (Stata Corp, College Station, TX). Standardized mean difference (SMD) and their 95% confidence interval (CI) were estimated. Results A total of 223 articles were evaluated and five articles were included in the meta-analysis. The results showed that there is a significant heterogeneity between the articles (p = 0.012, I-squared = 69.0%). The results of meta-analysis with a random model showed that there is no significant difference between male and female genders in terms of mean FHR (SMD = 0.04, 95%CI = -0.09-0.16, Z = 0.59, p = 0.553). Conclusion This systematic review and meta-analysis showed that even though male fetuses show faster FHR but such sex-related difference is minimal. Therefore, first-trimester FHR is not a reliable predictive test for fetal sex determination. Further studies are recommended to achieve a more precise conclusion. Trial registration PROSPERO: CRD42023418291.